Tantangan Strategi Pemasaran E-Commerce Dalam Mengelola Korean Wave, Brand Image, dan Kualitas Pelayanan Terhadap Niat Beli: E-Commerce Marketing Strategy Challenges in Managing the Korean Wave, Brand Image, and Service Quality on Purchase Intention - Desi Ratnasari; Risdiamon Risdiamon (OGZ Research & Publishing, 2026)
Abstract : The increasing popularity of Korean culture has shaped new consumer behavior and marketing dynamics in Indonesia’s digital market. Objective: This study aims to analyze the influence of the Korean Wave, brand image, and service quality on purchase intention in e-commerce platforms. Methods: Using a quantitative associative approach, data were collected from 105 e-commerce users in West Jakarta through a structured questionnaire. The data were analyzed using multiple linear regression with SPSS 22. Research Results: The results show that the Korean Wave, brand image, and service quality each have a positive and significant effect on purchase intention, both partially and simultaneously. Among these, the Korean Wave has the most dominant influence in shaping emotional attraction and consumer preferences toward Korean-related products. The study highlights the importance of integrating cultural trends, brand perception, and service excellence in developing sustainable e-commerce marketing strategies.